2016
DOI: 10.1371/journal.pone.0152277
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Livelihood Capital in Reducing Climatic Vulnerability: Insights of Australian Wheat from 1990–2010

Abstract: In many agricultural countries, development of rural livelihood through increasing capital is a major regional policy to adapt to climate change. However, the role of livelihood capital in reducing climatic vulnerability is uncertain. This study assesses vulnerability and identifies the effects of common capital indicators on it, using Australian wheat as an example. We calculate exposure (a climate index) and sensitivity (a wheat failure index) to measure vulnerability and classify the resilient and sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Comparing many different ways of performing the calculation of drought index, I selected six ways to express the drought index (DI) following the relevant literature that use at least three different calculation methods 18 53 54 55 56 . Firstly, the Soil Moisture Deciles-based Drought Index (SMDDI) of the Australian Bureau of Agricultural and Resource Economics and sciences Regions (ABARER) was used as the drought index.…”
Section: Methodology: Detailed Application Of the Framework In Austramentioning
confidence: 99%
“…Comparing many different ways of performing the calculation of drought index, I selected six ways to express the drought index (DI) following the relevant literature that use at least three different calculation methods 18 53 54 55 56 . Firstly, the Soil Moisture Deciles-based Drought Index (SMDDI) of the Australian Bureau of Agricultural and Resource Economics and sciences Regions (ABARER) was used as the drought index.…”
Section: Methodology: Detailed Application Of the Framework In Austramentioning
confidence: 99%
“…SLF employs various scaling and indexing methods to measure the natural, physical, financial, human and social capitals (Mengistu and Assefa, 2019). Huai (2016) reported that several countries have been encouraging their population to attain these capitals.…”
Section: Framework For Mahabalipuram Sustainable Tourismmentioning
confidence: 99%
“…financial capital allows agricultural producers to purchase physical capital such as machinery); diminish others (e.g. school fees increase human capital but diminish financial capital) (Huai, 2016;Quandt, 2018); enhance resilience (e.g. through strong bonding relations in social capital); and increase vulnerability (e.g.…”
Section: On Livelihoods and Capitalsmentioning
confidence: 99%